Reproductive health practices and use of health services among immigrant Indonesian women working in Malaysia - Rosnah Sutan; Pinta Pudiyanti Siregar (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE To describe the reproductive health practices of immigrant Indonesian women working in Malaysia and their accessibility to health services. METHODS A cross-sectional study using a validated self-administered questionnaire was conducted with 593 immigrant Indonesian workers who stayed in Malaysia for at least six months and within the reproductive age group. RESULTS About 13.5% of the respondents have used health facilities for reproductive health-related problems. Less than half of the respondents preferred to use public health facilities. Only 15% used treatment available in health facilities related to irregular menstrual cycles (34.6%), severe dysmenorrhea (58.7%) and nonspecific symptoms related to menstruation (31.7%). Family planning services were the most required health service. However, only 31.5% met the needs for family planning services. One-third of the respondents had sexual reproductive health problems and required treatment, but only 9.9% sought reproductive health services when needed. CONCLUSIONS Strategies to improve the accessibility to sexual reproductive health services requires a collaboration between the Indonesian government representatives in Malaysia and non-governmental organizations to address the reproductive health issues among immigrant Indonesian women in Malaysia. Health policy related to immigrant workers is needed in order to enhance the accessibility to women's health needs for universal health coverage.